Vitamin A supplementation for preventing morbidity and mortality in children from six months to five years of age - Imdad, Aamer (Cochrane Database Syst Rev, 2017)
BACKGROUND: Vitamin A deficiency (VAD) is a major public health problem in low‐ and middle‐income countries, affecting 190 million children under five years of age and leading to many adverse health consequences, including death. Based on prior evidence and a previous version of this review, the World Health Organization has continued to recommend vitamin A supplementation for children aged 6 to 59 months. There are new data available from recently published randomised trials since the previous publication of this review in 2010, and this update incorporates this information and reviews the evidence. OBJECTIVES: To assess the effects of vitamin A supplementation (VAS) for preventing morbidity and mortality in children aged six months to five years. SEARCH METHODS: In March 2016 we searched CENTRAL, Ovid MEDLINE, Embase, six other databases, and two trials registers. We also checked reference lists and contacted relevant organisations and researchers to identify additional studies. SELECTION CRITERIA: Randomised controlled trials (RCTs) and cluster‐RCTs evaluating the effect of synthetic VAS in children aged six months to five years living in the community. We excluded studies involving children in hospital and children with disease or infection. We also excluded studies evaluating the effects of food fortification, consumption of vitamin A rich foods, or beta‐carotene supplementation. DATA COLLECTION AND ANALYSIS: For this update, two reviewers independently assessed studies for inclusion and abstracted data, resolving discrepancies by discussion. We performed meta‐analyses for outcomes, including all‐cause and cause‐specific mortality, disease, vision, and side effects. We used the GRADE approach to assess the quality of the evidence. MAIN RESULTS: We identified 47 studies (4 of which are new to this review), involving approximately 1,223,856 children. Studies took place in 19 countries: 30 (63%) in Asia, 16 of these in India; 8 (17%) in Africa; 7 (15%) in Latin America, and 2 (4%) in Australia. About one‐third of the studies were in urban/periurban settings, and half were in rural settings; the remaining studies did not clearly report settings. Most of the studies included equal numbers of girls and boys and lasted about a year. The included studies were at variable overall risk of bias; however, evidence for the primary outcome was at low risk of bias. A meta‐analysis for all‐cause mortality included 19 trials (1,202,382 children). At longest follow‐up, there was a 12% observed reduction in the risk of all‐cause mortality for vitamin A compared with control using a fixed‐effect model (risk ratio (RR) 0.88, 95% confidence interval (CI) 0.83 to 0.93; high‐quality evidence). This result was sensitive to choice of model, and a random‐effects meta‐analysis showed a different summary estimate (24% reduction: RR 0.76, 95% CI 0.66 to 0.88); however, the confidence intervals overlapped with that of the fixed‐effect model. Nine trials reported mortality due to diarrhoea and showed a 12% overall reduction for VAS (RR 0.88, 95% CI 0.79 to 0.98; 1,098,538 participants; high‐quality evidence). There was no significant effect for VAS on mortality due to measles, respiratory disease, and meningitis. VAS reduced incidence of diarrhoea (RR 0.85, 95% CI 0.82 to 0.87; 15 studies; 77,946 participants; low‐quality evidence) and measles (RR 0.50, 95% CI 0.37 to 0.67; 6 studies; 19,566 participants; moderate‐quality evidence). However, there was no significant effect on incidence of respiratory disease or hospitalisations due to diarrhoea or pneumonia. There was an increased risk of vomiting within the first 48 hours of VAS (RR 1.97, 95% CI 1.44 to 2.69; 4 studies; 10,541 participants; moderate‐quality evidence). AUTHORS' CONCLUSIONS: Vitamin A supplementation is associated with a clinically meaningful reduction in morbidity and mortality in children. Therefore, we suggest maintaining the policy of universal supplementation for children under five years of age in populations at risk of VAD. Further placebo‐controlled trials of VAS in children between six months and five years of age would not change the conclusions of this review, although studies that compare different doses and delivery mechanisms are needed. In populations with documented vitamin A deficiency, it would be unethical to conduct placebo‐controlled trials.